Electrowetting‐Mediated Transport to Produce Electrochemical Transistor Action in Nanopore Electrode Arrays. Issue 18 (9th April 2020) - Kwon, Seung‐Ryong; Baek, Seol; Fu, Kaiyu; Bohn, Paul W.
Abstract: Understanding water behavior in confined volumes is important in applications ranging from water purification to healthcare devices. Especially relevant are wetting and dewetting phenomena which can be switched by external stimuli, such as light and electric fields. Here, these behaviors are exploited for electrochemical processing by voltage‐directed ion transport in nanochannels contained within nanopore arrays in which each nanopore presents three electrodes. The top and middle electrodes (TE and ME) are in direct contact with the nanopore volume, but the bottom electrode (BE) is buried beneath a 70 nm silicon nitride (SiN x ) insulating layer. Electrochemical transistor operation is realized when small, defect‐mediated channels are opened in the SiN x . These defect channels exhibit voltage‐driven wetting that mediates the mass transport of redox species to/from the BE. When BE is held at a potential maintaining the defect channels in the wetted state, setting the potential of ME at either positive or negative overpotential results in strong electrochemical rectification with rectification factors up to 440. By directing the voltage‐induced electrowetting of defect channels, these three‐electrode nanopore structures can achieve precise gating and ion/molecule separation, and, as such, may be useful for applications such as water purification and drug delivery. Abstract : Electrowetting‐mediated transistor action is realized using triple‐electrode‐embedded nanopore arrays, in which middle and top electrodes are in direct contact with electrolyte solution while bottom electrode is partially and temporarily accessible to the solution through defect nanochannels in the silicon nitride layer. Upon electric‐field‐induced wetting of the defect nanochannels, electrochemical rectification is obtained depending on the potential of the bottom electrode relative to the middle electrode.